AN APPRAISAL OF PSYCHOTROPIC DRUGS AND THEIR CONSEQUENCES AMONG THE CONSTRUCTION INDUSTRY WORKERS IN NIGERIA, ADAMAWA STATE CASE STUDY (Nigerian Journal of Technology, 2016)
This paper appraises the psychotropic drugs and its consequences, reactions on construction workers, responses to a given performance, which can be behavioral, perceptional, physiological, emotional and cognitive. This study was basically an appraisal of psychotropic drugs on construction workers, identification of types and effects. Structural questionnaires and oral interviews were used to collect data among construction workers. A simple statistical technique was used for the data analysis. The outcome of the study shows that majority (85%) of the population depend on drugs to achieve greater efficiency, acquire long lasting energy and alertness. The study further discovers the negative implications in terms of health risk and low productivity (i.e. caffeine(93%),create anxiety, disorder and sleep disruptions, Nicotines (73%) tobaccolosis, tramadol (85%) pelptic ulcer, marijuana(93%) mental sickness, codeine (73%)hyperactivity, Alcohol(51%)diabetes and hypertension), while poor or low quality job done is a sign of drug abuse intake by the workers. Others such as disobedient, quarrelling and abnormal behaviors are also sighs of drug abuse by the workers. This paper therefore, concludes that the use of psychotropic drugs by construction workers is real and is assuming an alarming rate in the industry. This study recommends collaborative effort between the construction firms and the drug regulatory agencies like National Drugs Law Enforcement Agency (NDLEA).Construction workers should undergo drug test process before given an employment, while seminars should be organized at least every quarter of the year on drug abuse or drug related issues or where special assistances in terms of professional advise and health intervention are given. http://dx.doi.org/10.4314/njt.v36i1.29